A Study on Integrity Testing for Platform-Pile Systems considering Wave Propagation. (16th May 2022) - Fu, Minghui; Lin, Meihong
Abstract : Platform-pile systems are typically used in bridge foundations and seaport structures. These systems are difficult to analyze using a conventional low-strain integrity test (LST) due to periodic oscillations. A staggered-grid finite-difference (SFD) method is proposed for a platform-pile system in soil and verified with ABAQUS and measured data. Different impact locations on the top surface of the platform and the lateral surface of the pile are analyzed, and parallel velocities are obtained at different locations. Choosing an appropriate impact location reduces the influence of the periodic oscillation signal; the impact locations at the center of symmetry are the best choices. At the same impact energy, the impact location should not be outside the cross section of the pile when the impact occurs on the top surface of the platform to achieve a meaningful damage signal. When the impact locations are on the lateral surface of the pile, the interferences are relatively small, and the damage vibration signal can be detected. The material and size of the hammer determine the impact duration and should be chosen to reduce the high-frequency influences and obtain reasonable data for analysis.